Effects of factors of a twin roller groundnut sheller on shelling performance - Srila, M.; Pachanawan, A.; Chuan-Udom, S. (International Journal of Agricultural Technology, 2021)
In order to develop a twin roller groundnut sheller, an understanding of this machine’s optimal performance factors is needed. Testing different shelling roller speeds and rolle - r clearances was investigated. The rollers used in this study were 50.80 mm in diameter and 200 mm long. The results showed that the optimal roller speed was 250 rpm, whilst the optimal roller speed differential was 35 rpm, providing a shelling efficiency of 81.15% and grain breakage of 9.80%. The optimal roller clearance was 10 mm providing a shelling efficiency of 88.30% with grain breakage of 5.26%